CCAFS South Asia Climate-Smart Agriculture Learning Platform Newsletter, May 2014 - CGIAR Research Program on Climate Change, Agriculture and Food Security (2014)
The CCAFS South Asia Climate-Smart Agriculture Learning Platform is a quarterly newsletter that features research highlights and field stories from CCAFS’ work in the South Asia region. In this edition, you can learn how CCAFS is working with the Agriculture Insurance Company in India to improve weather-based index insurance products for farmers. Read about how shopkeepers in Climate-Smart Villages are becoming communication gatekeepers by disseminating short educational videos on climate smart agriculture to their customers, many of whom are farmers. CCAFS South Asia is also developing a prioritization toolkit to help decision makers understand which climate smart interventions work best in a particular location.